Selection of efficient cleavage sites in target RNAs by using a ribozyme expression library. - Lieber, A (1995)
Inactivation of gene expression by antisense mechanisms in general and by ribozymes in particular is a powerful technique for studying the function of a gene product. We have designed a strategy for expression of ribozymes, for selection of accessible cleavage sites in target RNAs, and for isolation of ribozymes from a library of random sequences flanking the unique sequence of a hammerhead. The expression cassette for ribozyme genes is based on adenovirus-associated RNA. Alternatively, we used polymerase III or the T7 phage transcription machinery. The ribozyme sequences are positioned in the center of a stable stem-loop structure, allowing for a correctly folded ribozyme region within the expressed RNA. A library of ribozyme genes with random sequences of 13 nucleotides on both sides of the hammerhead was generated. As an example, ribozymes which are specific for seven sites within the mRNA or nuclear RNA of human growth hormone were selected and identified. Sequencing of ribozyme genes reamplified from the library confirmed not only the predicted cleavage sites but also the presence of different ribozyme variants in the library. In a test of the ribozyme variants for repression of growth hormone synthesis in a cellular assay, the strongest effect (more than 99% inhibition) was found for the variant with the shortest stretch of complementarity (7 and 8 nucleotides on either side) to the target RNA. This basic strategy seems to be applicable to the selection of suitable target sites and to the isolation of corresponding ribozymes for any mRNA of interest.